Decarbonizing maritime transport: A Ro-Pax case study - Zis, Thalis; Psaraftis, Harilaos N.; Tillig, Fabian; Ringsberg, Jonas W. (My University, 2020)
In an effort to reduce carbon emissions from international shipping, the International Maritime Organization (IMO) developed its initial strategy in April 2018 setting ambitious targets for the sector. According to the initial strategy, greenhouse gas (GHG) emissions from international shipping need to be reduced by at least 50% by 2050, and the CO2 emissions intensity by 40% by the year 2030, both compared to the 2008 levels. In order to achieve these goals, a combination of operational measures, investments in emissions abatement technology, and market-based measures will be necessary. The goals currently do not differentiate among different shipping sectors, and each sector faces different challenges. In this paper, we focus on short sea shipping (SSS), and on Ro-Pax services in particular that in general have not been examined thoroughly in the literature. We examine the emissions reduction potential of several measures, and we assess their efficacy compared with the targets set by the IMO initial strategy. The paper shows that the examined measures are not sufficient on their own to achieve the desired levels of reductions, and that a combination will be necessary, while technological solutions will need to be made more competitive through market based instruments.
Keywords: Short sea shipping; Ro-Pax shipping; Decarbonization; Maritime transport; Energy saving devices